Capturing language choice patterns of communities undergoing language shift : A qualitative inquiry - Norahim, Norazuna (Qualitative Research Association of Malaysia, 2011)
This paper discusses methodological frameworks to capture language choice patterns in communities undergoing language shift. An alternative framework employed in a study of a complex language contact situation is presented. The framework uses relevant literature in two inter-related fields: (i) the study of language choice and (ii) the study of social variation in language and linguistic change. Earlier and recent theories of language choice are adopted in data collection and analysis, i.e. the macro-sociological construct and the method of observation from the micro-interactional approach. From the study of social variation in language, the notion of speaker variation in language choice, and the implicational scaling technique are incorporated in analysis. It is also proposed that attempts to describe language choice patterns of multilingual communities should include theories of Bilingualism as a starting point of inquiry.